Schamberg Disease in a 54-Year-Old Chinese Woman - Alexander KC Leung; Amy AM Leung; Benjamin Barankin (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2015)
Schamberg disease, also known as Schamberg purpura or progressive pigmentary purpura, is characterized by orange-brown or reddish-brown macules/patches with overlaying purpuric spots simulating cayenne pepper". We report a 54-year-old Chinese woman with Schamberg disease presenting with purpuric macules and patches of varying sizes on the ankles, legs, and knees. The lesions were nonblanchable and nonpalpable and asymptomatic. Close inspection of the lesions revealed pinpoint petechiae resembling grains of cayenne pepper superimposed on the reddishbrown macules/patches. To our knowledge, Schamberg disease has not been reported in the scientific literature in Chinese patients.